The Benefits of in-betweenness: return migration of second-generation Chinese American professionals to China. Issue 12 (25th September 2016) - Wang, Leslie K.
ABSTRACT: In an era of growing transnational practices, this paper considers the trend of second-generation Chinese Americans who have 'returned' to the People's Republic of China (PRC) to work. Previous studies of return migration to China have focused on issues of ethnic and racial identity that arise during temporary homeland trips undertaken by those seeking to connect with ancestral and cultural origins. Accordingly, most research has highlighted the sense of cultural 'in-betweenness' experienced by Chinese Americans whose travels in the ancestral homeland bring an uncomfortable realisation that they are considered neither fully Chinese nor fully American. By contrast, my in-depth interviews with 52 second-generation Chinese American professionals in Beijing and Shanghai suggest that this liminality can be particularly useful in the workplace. I argue that first-world Chinese co-ethnics who work on a long-term basis in the PRC can uniquely leverage Western training with their assumed knowledge of Chinese culture to create personal economic advantage: a practice that I refer to as 'strategic in-betweenness'. Nonetheless, while participants described distinct career-related benefits to being Chinese American in the PRC, they also feared they would soon be replaced by high-skilled, Western-educated Chinese natives who are moving back to their home country in large numbers.